The Immense of Digital Divide: A Literature Review of Rural and Urban Schools’s Classroom Technologies in English Language Learning - Safira Safira; I G A Lokita Purnamika Utami; Ni Komang Arie Suwastini (Publikasi Indonesia, 2024)
This article aims to review various studies on the immense digital divide between rural and urban schools, specifically on classroom technologies in English language learning. We synthesize 26 from 2016-2023 discussing some external and internal issues regarding the differences between rural and urban schools’ classroom technologies in English language learning, including (a) Integration of Information and Communication of Technology (ICT) in English language learning in rural and urban school areas (b) Digital divide between the use of technologies in rural and urban school area, (c) External and internal factors (d) challenges. The majority of researchers in the study above used qualitative, quantitative, and mixed-method studies to find the result of the study through experiments, observations, and interviews. These recent studies have shown the relevant findings and results implemented in English language learning.